(untitled) (Czech Journal of International Relations, 2013)
Rob Dietz a Daniel W. O’Neil: Enough is Enough: Building a Sustainable Economy in a World of Finite Resources. 1st ed. Abingdon: Routledge, 2013, 256 stran, ISBN: 978-0-415-82095-0.